Regulatory effects and potential therapeutic implications of alarin in depression, and arguments on its receptor - Abebe, Endeshaw Chekol; Mengstie, Misganaw Asmamaw; Seid, Mohammed Abdu; Dejenie, Tadesse Asmamaw (Frontiers in Psychiatry, 2022)
Alarin is a pleiotropic peptide involved in a multitude of putative biological activities, notably, it has a regulatory effect on depression-like behaviors. Although further elucidating research is needed, animal-based cumulative evidence has shown the antidepressant-like effects of alarin. In light of its regulatory role in depression, alarin could be used as a promising antidepressant in future treatment for depression. Nevertheless, the available information is still insufficient and the therapeutic relevance of alarin in depression is still of concern. Moreover, a plethora of studies have reported that the actions of alarin, including antidepressant activities, are mediated by a separate yet unidentified receptor, highlighting the need for more extensive research. This review focuses on the current understanding of the regulatory effects and future therapeutic relevance of alarin on depression, and the arguments on its receptors.